Access to Basic Urban Amenities in India - Singh, M.B.; Mishra, Nitin Kumar (National Geographical Journal of India, 2022)
An access to basic urban amenities such as housing condition, drinking water, toilet facility, wastewater outlet, electricity and clean fuel etc. are considered important for leading a good and healthy life. About 13 percent of the urban households have no access to electricity, 16 percent have no access to safe drinking water and 27 percent have no access to toilet facility as per 2001 census in India. Indeed this proportion has declined significantly in 2011 but still 7 percent households have no access to electricity, 12 percent have no access to safe drinking water and 17 per cent have no access to toilet facility. About one- fifth of urban households are also not covered by any sewer facility. This study aims to analyse access to basic amenities at state level covering 28 states and 7 Union Territories. The regional disparity in terms of basic amenities closely follows the level of urbanisation. The states with low access to basic urban amenities are also characterised by low level of urbanisation.